Physical performance differences in female and male German elite youth basketball players according to selection status - Roesch, D.; Höner, O.; Huth, M.; Leyhr, D. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION Within talent identification in sports, test batteries assessing physical abilities and skills are commonly used to assist coaches in their efforts to identify promising young players (Johnston & Baker, 2020). For basketball particularly though, there is only limited evidence for the relevance of physical parameters in predicting future performance, especially as it pertains female youth players (Johnston et al., 2018; Mancha-Triguero et al., 2019). Therefore, the aim of the present study was to compare physical performance indicators of selected and non-selected female and male elite youth players competing at the national selection tournament of the German Basketball Federation.